SUPERVISI KEPALA SEKOLAH MENINGKATKAN KUALITAS TES BUATAN GURU - M. DJA'FAR HS. (Jurnal Evaluasi Pendidikan, 2013)
The objective of this research is to obtain information about the effect of principal supervision, school work climate, and mastery of the subject matter (history) toward quality of teacher test making. This research was conducted at senior high school in Jakarta Selatan involving 50 (fifty) persons of history teachers as the sample of this research. Data were collected using a valid and reliable questionnaire, and were analyzed using path analysis technique.The research finding show that: 1) the principal supervision has a direct positive influence to the quality of teacher test making, 2) the school work climate has a direct, and positive influence to the quality of teacher test making, 3) the mastery of subject matter (history) has a direct positive influence to thequality of teacher test making, 4) the principal supervision has a direct positive influence to the mastery of the subject matter, and 5) the school work climate has a direct positive influence to the mastery of subject matter (history).